ChemInform Abstract: An Aluminum Hydride that Functions Like a Transition‐Metal Catalyst. Issue 1 (17th December 2015) - Yang, Zhi; Zhong, Mingdong; Ma, Xiaoli; De, Susmita; Anusha, Chakkittakandiyil; Parameswaran, Pattiyil; Roesky, Herbert W.
Abstract: The aluminum hydride (ALH) efficiently catalyzes the hydroboration of aldehydes and ketones as well as the addition of trimethylsilyl cyanide.